The leftovers. The complete second season [videorecording (DVD)] - Lindelof, Damon, 1973-; Perrotta, Tom, 1961- (Leftovers (Television program)., 2016)
With Mapleton thrown into chaos at the close of season one, season two finds many of its residents searching for a fresh start. Kevin Garvey retires as police chief and moves his newly formed family to a small Texas town that seems to have been spared from the event that shook the rest of the world.